2024
DOI: 10.1002/smll.202306707
|View full text |Cite
|
Sign up to set email alerts
|

Organization of Carotenoid Aggregates in Membranes Studied Selectively using Resonance Raman Optical Activity

Natalia Hachlica,
Marta Stefańska,
Marzena Mach
et al.

Abstract: In living organisms, carotenoids are incorporated in biomembranes, remarkably modulating their mechanical characteristics, fluidity, and permeability. Significant resonance enhancement of Raman optical activity (ROA) signals of carotenoid chiral aggregates makes resonance ROA (RROA), a highly selective tool to study exclusively carotenoid assemblies in model membranes. Hence, RROA is combined with electronic circular dichroism (ECD), dynamic light scattering (DLS), molecular dynamics, and quantum‐chemical calc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…17,63 Importantly, AIRROA yields data only about CAR aggregates, as previously reported. 17,18,28 Therefore, supramolecular (3S,3 0 S)-AXT:BSA complexes, with the molar ratios of CAR to protein 1 : 1 and 3 : 1, were investigated using RR and resonance ROA (RROA) (Fig. 3).…”
Section: Roa Spectra Of (3s3 0 S)-axt:bsa Complexesmentioning
confidence: 99%
See 1 more Smart Citation
“…17,63 Importantly, AIRROA yields data only about CAR aggregates, as previously reported. 17,18,28 Therefore, supramolecular (3S,3 0 S)-AXT:BSA complexes, with the molar ratios of CAR to protein 1 : 1 and 3 : 1, were investigated using RR and resonance ROA (RROA) (Fig. 3).…”
Section: Roa Spectra Of (3s3 0 S)-axt:bsa Complexesmentioning
confidence: 99%
“…17,18,23 Thus, ECD and ROA show a rather unique sensitivity to CAR aggregation. 8,[17][18][19]23,28 It has been shown that CARs and their derivatives may aggregate due to their interaction with proteins, 29,30 for example lutein and zeaxanthin form aggregates during interaction with BSA and glutathione S-transferase. 30 In this work, we address the question of the carotenoid transport to cells (adipocytes) via albumins in an in vitro model system.…”
Section: Introductionmentioning
confidence: 99%
“…Up to now, bisignate or monosignate RROA spectral patterns have been proven to be beneficial in the study of varied molecular systems, including carotenoid aggregates, , metal complexes, ,, photoreceptor proteins, ,, and drugs . The sign and magnitude of RROA bands in the SES limit are determined by the ECD resonant transition, where the spectral pattern is similar to that of the parent RR spectrum (except for the sign).…”
mentioning
confidence: 99%